Pengaruh Smartphone Terhadap Prestasi Belajar Siswa Kelas X SMA Negeeri 5 Halmahera Utara - Flora Sumendap (Peneliti.net, 2022)
This study aims to determine the effect of smartphone use on student achievement in class X SMA Negeri 5 Halmahera Utara and increase student achievement when using smartphones. The results showed that in class X SMA Negeri 5 Halmahera Utara there were 23 students. And as many as 22 students have smartphones, there are even 11 students who have more than 1 smartphone. The use of smartphones on students has more negative effects than positive effects, the negative effects of smartphone use on fifth grade students include: (1) Many students who have smartphones have their free time taken up to play games, the internet (not to study). (2) When the learning process in the classroom, many students are not disciplined in learning, they do not pay attention to the teacher when explaining. (3) When given an assignment, they are not responsible for their duties. (4) Students rarely joke with their friends but are busy with games on their smartphones. (5) Some students often do not do their assignments on time